Prognostic factors related to clinical outcome following thrombectomy in ischemic stroke - Toan, Huynh Quoc; Quy, Nguyen Viet; Huynh, Le Vu; Phu, Hoang Hai; Nhan, Nguyen Thi (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Acute ischemic stroke continues to be one of the leading causes of disability and death and is a financial burden to an already taxed health care system. Early intra-arterial treatment with mechanical thrombectomy devices is safe and effective for reducing disability and is superior to standard treatment with intravenous thrombolysis alone for the treatment large artery occlusion stroke. Nevertheless prognostics factors need to be systematically analyzed in the context of these new therapeutic strategies. The aim of this study was to analyze prognostic factors related to clinical outcome following thrombectomy in ischemic stroke. Methods: This single - center prospective study included 84 patients with large vessel occlusion stroke, in the anterior and the posterior circulation. Sexes, age, time to recanalization were prospectively collected. Clinical outcome was assessed post treatment, day one and discharge by means of a NIHSS. Three months mRS evaluation was performed by an independent neurologist. The probability of good outcome at 3 months was assessed by forward stepwise logistic regression using baseline NIHSS score, Glasgow score (GCS) at entrance, hyperglycemia, dyslipidemia, NIHSS at discharge, ASPECT score, collateral scale, TICI scale and time to recanalization. All variables significantly associated with the outcome in the univariate analysis were entered in the model. The significance of adding or removing a variable from the logistic model was determined by the maximum likelihood ratio test. Odds - ratio (OR) and their 95% confidence intervals were calculated. Results: At 3 months 55.2% of patients had a mRS 0 - 2. Baseline NIHSS score (p = 0.001), hyperglycemia (p = 0.024), dyslipidemia (p = 0.016), ASPECT score at entrance (p = 0.005), Good collateral status (p = 0.046) were all factors significantly associated with 3 month clinical outcome. Collateral scale, TICI scale and time to final TICI were not correlated to 3 months outcome. Baseline NIHSS score (OR, 2.539; 95% CI, 1.278 - 5.049; p = 0.008), hyperglycemia (OR, 29.841; 95% CI, 1.050 - 848.183; p = 0.047), emerged as independent predictors of outcome at 3 months. Overall embolic complication rate was 5%, and symptomatic intracranial hemorrhage was 3.5%. Conclusions: There are multiple factors that determine the predictors of clinical outcome in patients who undenwent endovascular treatment. High NIHSS and hyperglycemia at admission were the two factor independently associated with a bad outcome at 90 days.